Bilateral hip joint arthroplasty in dysplastic hip arthritis in patients with osteopenia and osteoporosis - Loskutov, Oleksandr; Loskutov, Oleg; Syniehubov, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
In severe forms of dysplastic hip arthritis (DA) total hip arthroplasty is the most effective method of treatment. Objective: to investigate the results of bilateral hip arthroplasty in patients with dysplastic hip arthritis combined with osteopenia and osteoporosis. Methods: we examined 72 women with DA after bilateral total hip. The main group included 45 patients, who had DA combined with signs of osteopenia and osteoporosis. The control group consisted of 27 patients without signs of decreased mineral bone density. The mean age of patients in the main group was (51.5 ± 2.06) years, in the control group — (43.5 ± 2.25) years. Before surgery we assessed indexes: cortical, Singh, morpho-cortical, Noble, Spotorno. We analyzed the type of the femoral canal according to Spotorno and Dorr, type of dysplastic acetabulum. Results: 90 surgeries were made in the main group of patients, of which in 86 cases (95.6 %) cementless implants were used, in 3 cases (3.3 %) — hybrid fixation, in 1 case (1.1 %) — reverse hybrid fixation was used. The patients of the control group were undergone 54 operations of cementless hip replacement. The average evaluation of the results of treatment according to Harris hip score was 88.2 in the main group, in the control group — 89.1 points. Conclusions: during the planning of hip arthroplasty in patients with bilateral DA, it is necessary to take into account the x-ray anthropometric characteristics of the proximal femur, which allow to choose the design of the femoral component of the endoprosthesis and the type of its fixation, depending on the two-plane shape of the medullary canal. The use of threaded cementless cups allow to achieve a primary stable fixation of the acetabular component of the endoprosthesis in case of dysplastic deformation of the acetabulum even at decreased bone density.